Survival of probiotic Lactobacillus acidophilus in acidic environment is enhanced in the presence of Saccharomyces cerevisiae - Han, Le Nguyen; Dao, Dong Thi Anh (Vietnam Journal of Biotechnology, 2016)
A number of health benefits have been proved for probiotic bacteria by many studies and probiotics are increasingly incorporated into foods. However, these market preparations have shown low viability of probiotics in human digestion. Therefore, providing viable probiotic cells to the colon and maintaining their metabolic activity against severe conditions of human digestion are increasingly interested by many recent scientific researches. In this trend, our research showed that by creating a physical barrier, the presence of Saccharomyces cerevisiae (SC) in Lactobacillus acidophilus (LA) suspension can effectively protect probiotic cells from stresses of digestion. After 150 minutes in simulated gastric juice, the survival of LA is significant improved (p<0.05) by forming cell-cell contact with SC cells. The LA-only cells show that most cells die with viability of 0% due to low pH medium, compared with 11.025 ± 1.127% of LA+SC mixture. Besides, we found that the cell concentration ratio at 1:10 between SC and LA cells performs highest protective effects on the probiotic in the acidic environment with 10.122 ± 1.348% LA viability. This concentration ratio is the critical value because when the SC concentration is increasingly higher (SC÷LA concentration ratios higher than 1÷10), LA viability shows no significantly different increase. We also found that yeast cells with oxidized carbohydrates on cell’s surface have many adverse impacts on co-aggregation (4.003 ± 0.115% after 240-minute treatment) while non-viable yeast cells with damaged and denatured protein on cell’s surface still maintains a high percentage of co-aggregation with LA (26.050 ± 0.259% after 240-minute treatment).